INFLUENCE OF STOCK DENSITY ON DIGESTIVE ENZYME ACTIVITY (TRYPSIN), HEAT SHOCK PROTEIN 70 (HSP70), AND OXIDATIVE STRESS BIOMARKERS OF NARROW CLAWED CRAYFISH, ASTACUS LEPTODACTYLUS ESCHSCHOLTZ, 1823 (DECAPODA, ASTACIDAE) - Aksu, O.; Kutluyer, F.; Can, E.; Erisir, M.; Benzer, F. (Brill, 2016)
Stocking density causes changes in behaviour and physiology of aquatic animals and high density can cause oxidative damage in living cells. Therefore, experiments were designed to investigate the effects of stocking density on the oxidant-antioxidant response (glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT), and malondialdehyde (MDA)), digestive enzyme activity (trypsin), and heat shock protein 70 (HSP70) of narrow clawed crayfish (Astacus leptodactylus). The experiment was conducted to assess effects by stocking 3, 6, 9 and 12 crayfish/m(2). Crayfish were stocked into 12 fiberglass tanks, three replicates per treatment and fed for 45 days. Our results indicated that activity of GSH-Px, MDA, and GSH levels increased in hepatopancreas (p<0.05) and muscle tissues (p<0.05) with increasing stock concentration while CAT activity decreased (p<0.05). Trypsin and HSP70 insignificantly increased in haemolymph. In conclusion, oxidative stress biomarkers were negatively influenced by increased quantitative changes in stocking density.
Keywords: Experimental Pond Production; Heat-Shock; Cherax-Quadricarinatus; Cheliped Injuries; Redclaw Crayfish; Gene-Expression; Growth; Survival; Parastacidae; Glutathione